2012
DOI: 10.1177/0261018312444411
|View full text |Cite
|
Sign up to set email alerts
|

A challenge to liberalism? The communitarianism of the Big Society and Blue Labour

Abstract: This article explores how

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
(39 reference statements)
0
34
0
Order By: Relevance
“…Indeed this cuts across party lines. There are many parallels between the "Blue Labour" coproduction and cooperative agenda being pursued by Ed Milliband as leader of the opposition and localism and the Big Society (Sage 2012), and the eventual quiescence of Labour to the view that there is no alternative to austerity, suggest a permanent shift in policy framing has occurred in the UK. The "good times" of regeneration in the decade of growth will never return.…”
Section: Are We In a Post-regeneration Era?mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed this cuts across party lines. There are many parallels between the "Blue Labour" coproduction and cooperative agenda being pursued by Ed Milliband as leader of the opposition and localism and the Big Society (Sage 2012), and the eventual quiescence of Labour to the view that there is no alternative to austerity, suggest a permanent shift in policy framing has occurred in the UK. The "good times" of regeneration in the decade of growth will never return.…”
Section: Are We In a Post-regeneration Era?mentioning
confidence: 99%
“…Whilst the ideological nature of localism and the Big Society has been noted (Bednarek 2011;Buser 2012;Sage 2012) a continued criticism of these policies at a local level is that austerity has meant they are simply not resourced sufficiently to be successful. Analysis of where the cuts to the local government budget in England are falling have demonstrated that those areas that are seeing the biggest cuts are those which received substantial quantities of discretionary regeneration, economic development and sports and cultural funding under the New Labour governments.…”
Section: The Unequal Nature Of Localismmentioning
confidence: 99%
“…This also distinguishes the current approach from communitarianism, which would pay more attention to the wider structures surrounding the individual (Sage, 2012).…”
Section: Nudging In Alcohol Policymentioning
confidence: 99%
“…Over time its use in policy documents, ministerial statements and speeches appears to have declined somewhat, leading many to pronounce its demise. Nonetheless it has attracted a growing stream of academic analysis, seeking to understand the origins and meaning of the idea, particularly in relation to existing ideological traditions on the right and left, and its translation into a set of policy proposals and practical initiatives (see, for example, Alcock 2010, Smith 2010, Scott 2011, Taylor 2012, Sage 2012.…”
Section: Continuity and Change In Third Sector Policymentioning
confidence: 99%